Latin American cinema : a comparative history - Schroeder Rodríguez, Paul A., 1968- (University of California Press, 2016)
"A comparative history of Latin America's national cinemas over the course of five major periods: silent cinema, studio cinema, neorealism/art cinema, the New Latin American Cinema, and contemporary cinema. Close readings of approximately fifty films illustrate the major aesthetic, economic, and technological trends that define each period and the transitions between them. The selection of films reflects the tripartite division of film production in the region: 75 percent are from Brazil, Mexico, and Argentina; 25 percent are from countries other than the big three"--Provided by publisher.